Death wishes among older people assessed for home support and long‐term aged residential care. (17th November 2016) - Cheung, Gary; Edwards, Siobhan; Sundram, Frederick
Abstract : Objective: Death wishes in older people are common and may progress to suicidal ideation and attempts. This study used routinely collected data from the interRAI Home Care assessment to examine the prevalence and clinical predictors of death wishes in older New Zealanders assessed for home support and long‐term aged residential care. Methods: Data were collected from 35 734 people aged over 65 during 2012–2014. Chi‐squared analyses were used to determine significant relationships between the presence of death wishes and demographic factors, health and functional status, and emotional and psychosocial well‐being. A three‐step hierarchical logistic regression model was used to determine the predictive variables of death wishes, and odds ratios were calculated. Results: Death wishes were present in 9.5% of the sample. The following factors were significantly associated with death wishes: physical health (poor self‐reported health, recurrent falls, severe fatigue and inadequate pain control), psychological factors (depression, major stressors and anxiety), social factors (loneliness and decline in social activities) and impaired cognition. Depression (odds ratio = 2.54, 95% confidence interval = 2.29–2.81), loneliness (odds ratio = 2.40, 95% confidence interval = 2.20–2.63) and poor self‐reported health (odds ratio = 2.34, 95% confidence interval = 1.78–3.07) had the greatest odds ratios in the full model. Conclusions: Clinically significant depression alone cannot fully account for the development of death wishes in the elderly, and several factors are independently associated with death wishes. This knowledge can help clinicians caring for older persons to identify people who are most at risk of developing death wishes. Copyright © 2016 John Wiley & Sons, Ltd.